2021
DOI: 10.1142/s1363919621500912
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Team Innovation in Tech Start-Ups: The Role of Team Ambidexterity as Mediator Between Servant Leadership Behaviour and Team Innovation

Abstract: Early technology start-up faces a lot of problems such as leader mentality, ecosystem, lack of general knowledge, and innovation. One of the root causes is the absence of leadership role. This study is constructed to fill a research gap on the influence of servant leadership behaviour to team innovation in technology start-up. The authors propose team ambidexterity as mediator to enhance the role of servant leadership behaviour in fostering team innovation. We also investigate the team climate as a moderator t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…However, studies within other domains of research have identi ed a positive association between the two. Speci cally, in a variety of contexts and studies undertaken in different countries well support a positive relationship between AL and employees' innovative performance and aspects of CP (36, 50,52,53). Based on the discussion of theory, literature and previous empirical studies there is good reasons to expect to nd a similar pattern, that is, the practices of AL to be positively associated with CP of health professionals.…”
Section: Ambidextrous Leadership (Al)mentioning
confidence: 91%
“…However, studies within other domains of research have identi ed a positive association between the two. Speci cally, in a variety of contexts and studies undertaken in different countries well support a positive relationship between AL and employees' innovative performance and aspects of CP (36, 50,52,53). Based on the discussion of theory, literature and previous empirical studies there is good reasons to expect to nd a similar pattern, that is, the practices of AL to be positively associated with CP of health professionals.…”
Section: Ambidextrous Leadership (Al)mentioning
confidence: 91%
“…For example, Xu and Wang (2019) indicates how political climate, as a moderator, affects relationships between servant leadership and team-member exchange (mediator), and the relationship between team-member exchange and collective thriving (outcome). Antonio et al (2021) showed that team climate moderates the relationship between servant leadership and team innovation. Team climate enhances the moderating effect of servant leadership on ambidexterity in technology start-ups.…”
Section: Rq2 What Are the Mediators And Moderators Between Servant Le...mentioning
confidence: 99%
“…Servant leaders are genuinely focused on the development of their followers (Hu and Liden, 2011;Van Dierendonck, 2011), and it displays an altruistic commitment to helping followers to grow. Following the work of Yoshida et al (2014), where Servant leadership directly influences affect-based trust rather than cognitive-based within the team, and the study of Antonio et al (2021) on the impact of Servant Leadership on Team Ambidexterity, we hypothesize that:…”
Section: Servant Leadership and Team Ambidexteritymentioning
confidence: 99%
“…The expected outcome may vary depending on the context and the level difference of the organization (Schneider et al, 2013). Some examples of the outcome are creative performance (Si and Wei, 2012), firm performance (Baer and Frese, 2003), safety (Zohar and Tenne-Gazit, 2008), and innovation (Antonio et al, 2021). Kinnunen et al (2016) report a study on the relationship between Leadership and Team Climate.…”
Section: Team Climate and Leadership Behaviormentioning
confidence: 99%
See 1 more Smart Citation